UcTCRdb: An unconventional T cell receptor sequence database with online analysis functions - Dou, Yunsheng; Shan, Shiwen; Zhang, Jian (Frontiers in Immunology, 2023)
Unlike conventional major histocompatibility complex (MHC) class I and II molecules reactive T cells, the unconventional T cell subpopulations recognize various non-polymorphic ligands and typically exhibit simplified patterns of T cell receptor (TCR), rapid effector responses, and ‘public’ antigen specificities. Dissecting the recognition of the non-MHC antigens by unconventional TCRs can help to further understand unconventional T cell immunity. The small size and irregularities of the released unconventional TCR sequences are far from high-quality to support systemic analysis of unconventional TCR repertoire. Here we present UcTCRdb, a database that contains 672,333 unconventional TCRs collected from 34 corresponding studies in humans, mice, and cattle. In UcTCRdb, users can interactively browse TCR features of different unconventional T cell subsets in different species, search, and download sequences under different conditions. Additionally, basic and advanced online TCR analysis tools have also been integrated into the database, which will facilitate the discovery of unconventional TCR patterns for users of different backgrounds. UcTCRdb is freely available at http://uctcrdb.cn/.